2020
DOI: 10.1177/1751143720971541
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of 85 intensive care patients with Covid-19 in South London: A single centre observational study

Abstract: Background In March 2020, Covid-19 secondary to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) was declared a global pandemic. Methods This retrospective observational study included patients with Covid-19, managed in a single intensive care unit (ICU). We collected data on patient characteristics, laboratory and radiological findings and ICU management. Data are reported as median (interquartile range). Binary logistic regression modelling was used to identify variables at ICU admission associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…After reviewing the full texts of 938 articles, 71 COVID-19 studies were included in the meta-analysis ( Figure 1A ). 1 - 3 , 13 , 27 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After reviewing the full texts of 938 articles, 71 COVID-19 studies were included in the meta-analysis ( Figure 1A ). 1 - 3 , 13 , 27 …”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full texts of 938 articles, 71 COVID-19 studies were included in the meta-analysis (Figure 1A). 1-3,13,27-94 Similarly, 7742 articles on ACE2-associated (SARS-CoV-1, influenza H1N...…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, in a study conducted by Isted et al . 34 . , non-survivors and survivors did not have different APACHE II scores.…”
Section: Discussionmentioning
confidence: 99%
“…Zou et al (2020 ) also found the APACHE II scores as an independent predictor of mortality in hospitalised patients, consistent with our study[ 34 ]. On the contrary, Isted et al (2020) from the UK reported no differences among APACHE II scores among survivors and non-survivors [ 35 ]. Admission SOFA scores and admission D-Dimer was found to be independent predictors of mortality by Zhou et al (2020) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%